Descriptive psychopathology : the signs and symptoms of behavioral disorders - Taylor, Michael Alan, 1940-; Vaidya, Nutan Atre; Cambridge eBooks (Cambridge : Cambridge University Press, 2009)
In order to accurately describe and diagnose psychiatric illness, practitioners require in-depth knowledge of the signs and symptoms of behavioral disorders. Descriptive Psychopathology provides a broad review of the psychopathology of psychiatric illness, beyond the limitations of the DSM and ICD criteria. Beginning with a discussion of the background to psychiatric classification, the authors explore the problems and limitations of current diagnostic systems. The following chapters then present the principles of psychiatric examination and diagnosis, described with accompanying patient vignettes and summary tables, and related to different diagnostic concerns. A thought-provoking conclusion proposes a restructuring of psychiatric classification based on the psychopathology literature and its validating data. Written for psychiatry and neurology residents, clinical psychologists, behavioral neurologists, clinical psychology students and psychiatric nurse practitioners, it is invaluable to anyone who accepts the responsibility for the care of patients with behavioral syndromes.
Beyond the DSM and ICD : a rationale for understanding and using descriptive psychopathology -- A history of psychiatric classification -- The brain and psychopathology -- The neuropsychiatric evaluation : principles of descriptive psychopathology and the diagnostic process -- The neuropsychiatric evaluation : examination style, structure, and technique -- Psychopathology of everyday behavior and general appearance -- Disturbances of motor function -- Disturbances in emotional experience -- Disturbances in speech and language -- Perceptual disturbances -- Delusions and abnormal thought content -- Obsessive-compulsive behaviors -- Cognitive testing and the psychopathology of cognitive dysfunction -- Personality -- Abnormal trait behaviors : personality disorder -- An evidence-based classification.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Psychodiagnostics; Neurobehavioral disorders -- Diagnosis; Psychology, Pathological; Electronic books